SHIP1 Activator AQX-1125 Regulates Osteogenesis and Osteoclastogenesis Through PI3K/Akt and NF-κb Signaling - Xie, Xudong; Hu, Liangcong; Mi, Bobin; Panayi, Adriana C.; Xue, Hang; Hu, Yiqiang; Liu, Guodong; Chen, Lang; Yan, Chenchen; Zha, Kangkang; Lin, Ze; Zhou, Wu; et al. (Frontiers in Cell and Developmental Biology, 2022)
With the worldwide ageing population, the prevalence of osteoporosis is on the rise, particularly the number of postmenopausal women with the condition. However, the various adverse side effects associated with the currently available treatment options, underscore the need to develop novel therapies. In this study, we investigate the use of AQX-1125, a novel clinical‐stage activator of SHIP1, in OVX-induced bone loss, identifying a protective role. We find that the effect was likely due to increased osteogenesis and mineralization and decreased osteoclastogenesis caused by AQX-1125 in a time-and dose-dependent manner. The effect against bone loss is identified to be SHIP1 dependent, as pretreatment of BMSCs and BMMs with SHIP1 RNAi could greatly diminish the osteoprotective effects. Furthermore, SHIP1 RNAi administration in vivo induced significant bone loss and decreased bone mass . Mechanistically, AQX-1125 upregulated the expression and activity of SHIP1, by upregulating the phosphorylation of PI3K and increasing Akt expression to promote osteoblast-related gene expression including Alp, cbfa1, Col1a1 and osteocalcin. NF-κB signaling was also inhibited through suppression of the phosphorylation of IκBα and P65 induced by RANKL resulting in diminished osteoclastogenesis. Taken together, our results demonstrate that AQX-1125 may be a promising candidate for preventing bone loss.